Potencial antimicrobiano e atividade antioxidante de espécies do gênero Lippia (Verbenaceae) do semi-árido baiano - Mercês, Manuela Dória das (2011)
The use of medicinal plants is an alternative therapy for many communities. With the emergence of microorganisms resistant to conventional drugs is necessary to search for new compounds with antibiotic properties. Lippia species of the genus have been used in folk medicine to treat respiratory and gastric diseases, fever, such as tranquilizers and also because of its recognized antimicrobial properties. This study aimed to analyze the antimicrobial and antioxidant potential of methanol extract of L. hermanoides, L. morii and L. subracemosa. The species were collected in semi-arid region and were evaluated against Staphylococcus aureus (CCMB 262) resistant to streptomycin and dihydrostreptomycin, Escherichia coli (CCMB 261) sulfonamide-resistant and sensitive to trimethoprim) Pseudomonas aeruginosa (CCMB 268), Bacillus cereus (CCMB 282) and yeasts, Candida albicans (CCMB 286) and Candida parapsilosis (CCMB 288), both resistant to fluconazole and amphotericin B, the method of minimum inhibitory concentration (MIC). Subsequently, the samples were subjected to the test of antioxidant activity by DPPH free radial method and also analyzed the content of total phenolics and flavonoids content. This study showed that the species L.hermanoides, L. morii and L. subracemosa collected in semi-arid region have antimicrobial activity against microorganisms tested and antioxidant potential.